1995
DOI: 10.1177/004728759503300304
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Awareness and Familiarity with a Destination: The Central Florida Case

Abstract: This study is based on the theoretical background of the consumer's buying process incorporating product awareness, familiarity, interest, and purchase. Using a sample of 750 U.S. households, a series of hypotheses were tested to analyze whether consumer aware ness and familiarity with Central Florida as a vacation destination had an impact on the consumer's destination image and on the interest and likelihood to visit it. The results indicate that those who were familiar with Central Florida (i.e., had previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
391
3
42

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(460 citation statements)
references
References 11 publications
24
391
3
42
Order By: Relevance
“…Quan and Wang (2004) investigated primary and secondary trip motivations and show that, in addition, food can be seen as primary trip motive and has a significant influence on the overall image of destinations. Milman and Pizam (1995) and Goossens (2000) discussed and investigated destination image and the depth of influence it has on travel motivation, showing the complex ways in which push factors are combined in influencing destination choice.…”
Section: Urban Travel Motivationmentioning
confidence: 99%
“…Quan and Wang (2004) investigated primary and secondary trip motivations and show that, in addition, food can be seen as primary trip motive and has a significant influence on the overall image of destinations. Milman and Pizam (1995) and Goossens (2000) discussed and investigated destination image and the depth of influence it has on travel motivation, showing the complex ways in which push factors are combined in influencing destination choice.…”
Section: Urban Travel Motivationmentioning
confidence: 99%
“…Researchers have found that visitors have more positive and favorable images of a destination than non-visitors (Awaritefe, 2004;Fakeye & Crompton, 1991;Hughes & Allen, 2008;Leisen, 2001;Milman & Pizam, 1995). Visitors score significantly higher than non-visitors on image attributes, such as social opportunities and attractions; infrastructure, food, and friendly people; and bars and evening entertainment, because contacts with residents and the use of the destination's facilities could help visitors create a more complex and differentiated image (Fakeye & Crompton, 1991).…”
Section: Visitors Vs Non-visitorsmentioning
confidence: 99%
“…Qu et al (2011) argue that a destination image is influenced by cognitive and affective associations stored in visitors' memories. Authors with similar perspectives refer to "image" as a dynamic construct, a set of beliefs and impressions concerning a particular product or experience (Kotler et al, 2006;Milman & Pizam, 1995).…”
Section: Destination Image and Brandingmentioning
confidence: 99%
“…Intrinsic values, supported by some authors (Kotler, Gertner, Rein, & Haider, 2006;Milman & Pizam, 1995;Qu, Kim, & Im, 2011;Valle, Mendes, & Guerreiro, 2012) were considered, namely, (a) genesis (related to the origins of the PA) and (b) conception (related to the way in which stakeholders view and intrinsically conceptualize the PA).…”
Section: Introductionmentioning
confidence: 99%